Keputusan Pekerja Lansia tetap Bekerja Pascapensiun dan Kaitannya dengan Kebahagiaan - Jamalludin, Jamalludin (Fakultas Ekonomi Universitas Samudra, 2021)
This study aims to determine the contribution of pension insurance, health needs, and type of work to the decision of elderly workers to continue working post-retirement and its relationship with happiness. The Indonesian Family Life Survey (IFLS) 2007 and IFLS 2014 were used as data, with an analysis unit of workers aged 52-65 years old in 2007. The analysis used is binary logistic regression and the Wilcoxon sign rank test. Pension insurance and work in the type of work with a large concentration demands a negative effect on the tendency of the elderly to continue working. Health care needs are fulfilled and work in the type of work with great physical demands has a positive effect on the tendency of the elderly to work. There is a difference in the level of happiness in the elderly when they are still actively working with when they are not working.